How institutional support enhances teacher engagement in online teaching: chain mediation effects of digital self-efficacy and negative emotions - Liu, Dongping; Sun, Zhonghua; Cui, Yulu (Frontiers in Psychology, 2025)
Online teaching has become a cornerstone of educational continuity in the era of digital education. However, sustaining teacher engagement in online teaching persists as a critical barrier to teacher sustainability. This study aims to investigate how institutional support enhances teachers’ work engagement through digital self-efficacy and negative emotions in online teaching. Participants were 232 K-12 teachers from different schools in China. A structural equation modeling (SEM) was used to confirm the initial model hypotheses regarding the relationship between variables. The findings show that institutional support is positively related to teacher work engagement, with digital self-efficacy and negative emotions as significant mediators. Finally, implications for educational administrators and teachers were discussed, with a focus on the importance of focused interventions that address teachers’ emotional and technological needs to improve their work engagement in online teaching.